Pengaruh Kepemimpinan Transformasional, Disiplin Kerja dan Komunikasi Terhadap Kinerja Pegawai pada Dinas Pendidikan Kepulauan Riau - Arman Syarif; Khairul Riza (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
Purpose: The purpose of writing this journal is to determine the effect of transformational leadership on employee performance in the Kepulauan Riau Education Office, the effect of work discipline on employee performance in the Kepulauan Riau Education Office, the influence of communication on employee performance in the Kepulauan Riau Education Office. Methodology: This type of research is quantitative research, namely research methods based on positivism philosophy, used to examine certain populations or samples. Results: The results showed that transformational leadership had a positive and significant effect on employee performance at the Kepulauan Riau Education Office. This can be seen from the significant transformational leadership (X1) 0,000 <0.05. And the value of thitung is greater than ttabel (3,925 > 1.99394), then H0 is rejected and H1 is accepted. Work discipline has a positive and significant effect on employee performance at the Kepulauan Riau Education Office. This can be seen from the significant work discipline (X2) 0.021 <0.05. And the value of thitung is greater than ttabel (2,353> 1,99394), then H0 is rejected and H2 is accepted. Communication (X3) has a positive and significant effect on employee performance at the Kepulauan Riau Education Office. This can be seen from significant communication (X1) 0.025 <0.05. And the value of thitung is greater than ttabel (2,289> 1,99394), then H0 is rejected and H3 is accepted. Transformational leadership, work discipline, communication jointly significantly affects employee performance variables because the Fhitung value is 1563,214 which is greater than Ftabel of 2.73. And a significant level of 0,000> 0.05.